Sočasna sečnja in helikoptersko spravilo lesa z Ljubljanskega Grajskega griča - Triplat, Matevž (Gozdarski vestnik, 2025)
Helicopter harvesting is one of the most modern and technologically and organisationally demanding methods of timbharvesting, which is particularly suitable for hard-to-reach areas where other technologies are not feasible or would have tohigh an impact on the environment. In early January 2025, a simultaneous tree felling and helicopter harvesting operatiowas carried out in Ljubljana‘s city centre. The project required careful organisation and coordination of various professionaincluding arborists, forestry experts, loggers, a pilot and security services. Before the arrival of the helicopter, a detaileassessment of the terrain had to be carried out, trees to be felled had to be marked and appropriate safeguards had to be pin place to ensure the safety of everyone involved, as well as the citizens and visitors to Ljubljana. The harvesting procesitself was based on a high level of precision and coordination between the arborists and the helicopter pilot, as it was crucithat each lift was carried out in a controlled and safe manner. The advantages of this type of harvesting are reduced impacon the soil and the stand, reduced erosion and the possibility of harvesting timber from areas where traditional methods anot feasible. Although the use of helicopters in forestry is not new, its use in Slovenia is only just beginning. The carried-oproject was thus an important test case for future possibilities of introducing such methods in Slovenia. The experience gaineis valuable for the further development of forestry technologies. The analysis of the implementation contributes to a bettunderstanding of the factors affecting the efficiency and safety of such operations. Key words:
Keywords: harvesting; helicopter; helikopter; organisation; organizacija; protective forest; spravilo lesa; varovalni gozd; zaščitna funkcija